2022
DOI: 10.1111/apt.16952
|View full text |Cite
|
Sign up to set email alerts
|

Review article: latent tuberculosis in patients with inflammatory bowel diseases receiving immunosuppression—risks, screening, diagnosis and management

Abstract: Summary Background One quarter of the world's population has latent tuberculosis infection (LTBI). Systemic immunosuppression is a risk factor for LTBI reactivation and the development of active tuberculosis. Such reactivation carries a risk of significant morbidity and mortality. Despite the increasing global incidence of inflammatory bowel disease (IBD) and the use of immune‐based therapies, current guidelines on the testing and treatment of LTBI in patients with IBD are haphazard with a paucity of evidence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 170 publications
(355 reference statements)
0
14
0
Order By: Relevance
“…We read with interest the article by Fehily et al 1 It reviewed the available guidelines on latent tuberculosis (LTB) management and risk of reactivation with immunosuppressive therapy used in patients with inflammatory bowel disease (IBD). The authors identified major gaps in evidence especially with newer IBD treatments.…”
Section: Editorsmentioning
confidence: 99%
“…We read with interest the article by Fehily et al 1 It reviewed the available guidelines on latent tuberculosis (LTB) management and risk of reactivation with immunosuppressive therapy used in patients with inflammatory bowel disease (IBD). The authors identified major gaps in evidence especially with newer IBD treatments.…”
Section: Editorsmentioning
confidence: 99%
“…To prevent TB reactivation complications, our review recommends proactive screening for LTBI in patients undergoing immunesuppressive therapy. 2 Further, surveillance should be considered if a patient reports a new TB exposure. 2 However, due to lymphocyte migration inhibition, S1P modulators could theoretically affect LTBI testing results.…”
Section: Editorsmentioning
confidence: 99%
“…2 Further, surveillance should be considered if a patient reports a new TB exposure. 2 However, due to lymphocyte migration inhibition, S1P modulators could theoretically affect LTBI testing results. Reassuringly, in a retrospective case series of 222 MS patients, only 1 of 13 patients on fingolimod returned an equivocal quantiferon gold (QF-Gold) result even though almost all demonstrated lymphopenia.…”
Section: Editorsmentioning
confidence: 99%
“…The low sensitivity of LTBI screening tests (tuberculin skin test (TST) and the interferonγ-release assay (IGRA)) when performed under immunosuppressive therapies [7,9] has been posed as one of the potential factors that increase the risk of active TB during anti-TNF treatment. Different strategies have been developed to improve the performance of immunodiagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been developed to improve the performance of immunodiagnostic tests. Early screening, performed ideally at inflammatory bowel disease (IBD) diagnosis or in the absence of immunosuppressive drugs [9,10], increases its sensitivity for detecting LTBI. Adding a second TST seven to 14 days after a first negative test increases the LTBI diagnostic yield by 5-25% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%